Mesenchymal stem cell-derived extracellular vesicles attenuate kidney inflammation - Eirin, Alfonso (Kidney Int, 2017)
Mesenchymal stem/stromal cells (MSCs) have distinct capability for renal repair, but may have safety concerns. MSC-derived extracellular vesicles emerged as a novel non-cellular alternative. Using a porcine model of metabolic syndrome and renal artery stenosis we tested whether extracellular vesicles attenuate renal inflammation, and if this capacity is mediated by their cargo of the anti-inflammatory cytokine interleukin (IL)10. Pigs with metabolic syndrome were studied after 16 weeks of renal artery stenosis untreated or treated four weeks earlier with a single intrarenal delivery of extracellular vesicles harvested from adipose tissue-derived autologous MSCs. Lean and sham metabolic syndrome animals served as controls (seven each). Five additional pigs with metabolic syndrome and renal artery stenosis received extracellular vesicles with pre-silenced IL10 (IL10 knock-down). Single-kidney renal blood flow, glomerular filtration rate, and oxygenation were studied in vivo and renal injury pathways ex vivo. Retention of extracellular vesicles in the stenotic-kidney peaked two days after delivery and decreased thereafter. Four weeks after injection, extracellular vesicle fragments co-localized with stenotic-kidney tubular cells and macrophages, indicating internalization or fusion. Extracellular vesicle delivery attenuated renal inflammation, improved medullary oxygenation and fibrosis. Renal blood flow and glomerular filtration rate fell in metabolic syndrome and renal artery stenosis compared to metabolic syndrome, but was restored in pigs treated with extracellular vesicles. These renoprotective effects were blunted in pigs treated with IL10-depleted extracellular vesicles. Thus, extracellular vesicle-based regenerative strategies might be useful for patients with metabolic syndrome and renal artery stenosis.